(untitled) (Research, Society and Development, 2020)
This work analyzed the labels of medicinal teas from formal trade, according to the specific legislation. Thirty samples of herbal drugs included in the Form of Phytotherapeutics of the Brazilian Pharmacopeia were photographed in commercial establishments in Rio de Janeiro state, Brazil, and analyzed according to the Resolution of Anvisa RDC 26/2014 and the Form. Information related to the botanical nomenclature, plant part, guidelines for preparation, warnings, claims, and orientations for use was inconsistent with the official standards in most samples, and 77% were marketed as food products, although the studied species are not regulated for the commercialization in the food area. The consumption of herbal products in disagreement with the official recommendations may cause toxic effects or lack of the expected benefits. The irregularities identified suggest the absence or failure in quality control and a lack of concern for the scientific botanical nomenclature, exposing the public health to risks.